The potential of biochar and compost from sugarcane bagasse on growth, yield, nutrient uptake of shallot and properties of an Inceptisol - Zu'amah, Hidayatuz; Handayani, Cicik Oktasari; Dewi, Triyani; Arianti, Forita Dyah; Beti, Jajuk Aneka; Jufri, Akhmad; Rosjidi, Mochamad; Sahara, Dewi; Maro'ah, Siti; Syamsiyah, Jauhari (Journal of Degraded and Mining Lands Management, 2025)
Excessive pesticide use and intensive shallot farming to satisfy high market demand can degrade soil quality and harm environmental sustainability. Sustainable agricultural practices, such as biochar and compost are alternatives to ensure long-term soil productivity and fertility. This study aimed to investigate the ability of biochar and compost made from bagasse waste to improve shallot growth, yield, nutrient absorption, and soil quality. The research used a factorial randomized block design in a greenhouse. The first factor was the application of biochar and compost (K1 = compost, K2 = biochar, K3 = biochar-compost (1:4/w:w) and K4 = biochar-compost (1:2/w:w), and the second factor was the dose of NPK fertilizer (0%, 50%, and 100% of the recommended dose). The planting medium used was an Inceptisol from shallot fields in Sukaharjo, Central Java. The variables measured included plant growth, yield components, soil chemical properties, and levels of N, P, and K in plants. The results showed that the combination of compost with 100% NPK fertilizer gave better results in plant growth, fresh and dry weight of plants and tubers, increased organic C, total N, and CEC of the soil, and increased the absorption of N, P, and K by plants.